Respuestas
Respuesta dada por:
2
Solución:
(x)(x+2) = 80
x² + 2x = 80
x² + 2x - 80 = 0 ---> ecuación cuadrática
Por formula general.
x² + 2x - 80 = 0
![x=\dfrac{- \ 2 \pm \sqrt{2^{2} -4(1)(-80)}}{2(1)}\\ \\ \\
x=\dfrac{- \ 2 \pm \sqrt{4 +320}}{2}\\ \\ \\
x=\dfrac{- \ 2 \pm \sqrt{324}}{2}\\ \\ \\
x=\dfrac{- \ 2 \pm18}{2} x=\dfrac{- \ 2 \pm \sqrt{2^{2} -4(1)(-80)}}{2(1)}\\ \\ \\
x=\dfrac{- \ 2 \pm \sqrt{4 +320}}{2}\\ \\ \\
x=\dfrac{- \ 2 \pm \sqrt{324}}{2}\\ \\ \\
x=\dfrac{- \ 2 \pm18}{2}](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B-+%5C+2+%5Cpm+%5Csqrt%7B2%5E%7B2%7D+-4%281%29%28-80%29%7D%7D%7B2%281%29%7D%5C%5C+%5C%5C++%5C%5C+%0Ax%3D%5Cdfrac%7B-+%5C+2+%5Cpm+%5Csqrt%7B4+%2B320%7D%7D%7B2%7D%5C%5C+%5C%5C++%5C%5C+%0Ax%3D%5Cdfrac%7B-+%5C+2+%5Cpm+%5Csqrt%7B324%7D%7D%7B2%7D%5C%5C+%5C%5C++%5C%5C+%0Ax%3D%5Cdfrac%7B-+%5C+2+%5Cpm18%7D%7B2%7D)
De la ecuación tenemos que:
![x_1=\dfrac{- \ 2 + 18}{2}=8\\ \\ \\
x_2=\dfrac{- \ 2 - 18}{2}=-10 x_1=\dfrac{- \ 2 + 18}{2}=8\\ \\ \\
x_2=\dfrac{- \ 2 - 18}{2}=-10](https://tex.z-dn.net/?f=x_1%3D%5Cdfrac%7B-+%5C+2+%2B+18%7D%7B2%7D%3D8%5C%5C+%5C%5C++%5C%5C+%0Ax_2%3D%5Cdfrac%7B-+%5C+2+-+18%7D%7B2%7D%3D-10)
RTA: x = {8 ; -10}
(x)(x+2) = 80
x² + 2x = 80
x² + 2x - 80 = 0 ---> ecuación cuadrática
Por formula general.
x² + 2x - 80 = 0
De la ecuación tenemos que:
RTA: x = {8 ; -10}
Adjuntos:
![](https://es-static.z-dn.net/files/dfb/3abf00d45f1ffb7cd9da5094cdb831d0.png)
abideloz1802:
Gracias de nuevo!
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años